Force requirement profiles for swing to strength hold elements on still rings in men´s artistic gymnastics - Merz, C.; Aarts, M.; Lehmann, T.; Seemann-Sinn, A.; Pluk, A.; Naundorf, F. (Sports Biomechanics, 2025)
Swing to strength hold elements are important for a top ranking on still rings, require a high level of upper body strength of the gymnasts and have not yet been scientifically investigated. Therefore, the aim of this study was to determine force requirement profiles for these elements using a dynamometric measuring system. Two force sensors attached to the cables of each ring and synchronised with video recorded the forces exerted by the gymnast. For eight swing to strength hold elements (Uprise backward to support scale straddled, Uprise backward to swallow, Uprise backward to cross, Honma to cross, Uprise backward to support scale, Kip to cross, Back kip to swallow and Uprise backward to inverted cross), the variables maximal force (Fmax), minimal force (Fmin), time over Fhold (t1-3), rate of maximal force development (RFD) and impulse (p) were analysed. Honma to cross shows the highest force requirements (Median: Fmax = 120.4% BW, Fmin = 109.8% BW, t1-3 = 882 ms, RFD = 143.93% BW/s, p = 9.85% BWs) whereas back kip to swallow shows the least (Fmax = 102.3% BW, RFD = 34.99% BW/s and p = 0.84% BW/s). The biomechanical demand profiles can be used to provide feedback to coaches and gymnasts. In future research, they should be extended with kinematic and electromyographic data.